2023
DOI: 10.1039/d3bm00174a
|View full text |Cite
|
Sign up to set email alerts
|

Green polymer hydrogels from a natural monomer with inherent antioxidative capability for efficient wound healing and spinal cord injury treatment

Abstract: Development of polymeric hydrogels with multiple functions (adhesiveness, self-healability, antioxidation, etc.) through one-step green polymerization of naturally occurring small molecules in water is critical for various biomedical applications and clinical...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Additionally, some researchers have successfully prepared a polylipoic acid-sodium lipoate hydrogel (PLAS) with desirable mechanical properties, easy injectability, and sufficient adhesion. Animal experiments have revealed that PLAS can effectively eliminate cellular ROS, thereby promoting recovery from spinal cord injury ( 149 ).…”
Section: Ros Removal In Materials Science Developmentmentioning
confidence: 99%
“…Additionally, some researchers have successfully prepared a polylipoic acid-sodium lipoate hydrogel (PLAS) with desirable mechanical properties, easy injectability, and sufficient adhesion. Animal experiments have revealed that PLAS can effectively eliminate cellular ROS, thereby promoting recovery from spinal cord injury ( 149 ).…”
Section: Ros Removal In Materials Science Developmentmentioning
confidence: 99%
“…Liu et al constructed a gelatin-modified hydrogel laden with NSCs and albumin-incubated CeO2 nanoparticles, which could promote neurogenesis via alleviating oxidative stress microenvironments and improving the viability of encapsulated NSCs [112]. The hydrogel prepared by Du et al via polymerization of α-lipoic acid had inherent antioxidant capacity and can effectively provide wound-healing and spinal cord injury treatment, removing ROS from the injury site [113]. Thus, the antioxidant function of injectable hydrogels provides a new therapeutic idea for the treatment of SCI.…”
Section: Antioxidantmentioning
confidence: 99%
“…This holistic approach to hydrogel design not only effectively modulated oxidative stress and inflammation at the application site but also facilitated the migration and differentiation of NSCs into neurons, thereby amplifying the regenerative potential of the hydrogel system. Furthermore, biomaterials with similar structures that lack conductivity properties have also shown promise as SCI treatments [44] …”
Section: Ros‐targeted Biomaterials For Sci Treatmentmentioning
confidence: 99%
“…Furthermore, biomaterials with similar structures that lack conductivity properties have also shown promise as SCI treatments. [44] Inspired by the ROS-cleavable ability of thioketal diamine, Li et al designed and fabricated a thioketalcontaining ROS-scavenging hydrogel. [45] Several classical analytical techniques, such as DPPH scavenging analysis, H 2 O 2 scavenging analysis, and O 2 − scavenging analysis, were used to assess the ROS-clearing functions of the hydrogel.…”
Section: Organic Ros-core Biomaterials For Sci Treatmentmentioning
confidence: 99%